Sejarah perkembangan sistem jalan raya di Sabah, 1946–1975 / Sitti Asmah Ammituh - Sitti Asmah , Ammituh (2016)
Social development in Sabah includes the construction and upgrading of roads and is important for the state’s economic activities. Further, the daily activities of the people of Sabah has direct relationship with the system of transportation, especially roads. After the British gained control of Sabah in 1946 roads were given much attention, and this was particularly evident under the Malaysia plan starts from 1963 until 1975. The economic and social needs prompted the administrators to improve the roads facilities. This study will discuss the development of roads in Sabah under the British colonial administration and after the state joined the federation of Malaysia in the period between 1946 and 1975. This study seeks to explain if the roads in Sabah involves the building of new roads or merely the upgrading of existing roads. This study is based on the examination of primary sources such as the Colonial Office record, Dominion Office record, ministry and department Files, Annual Reports and newspapers. The study also examines secondary source such a books, magazine and journals. This dissertation has found that the road development is evident under the British colonial government and then rose slowly but continuously when Sabah joined the federation. This is obvious from an examination of the building of roads in the state. The length of roads increased considerably based on the construction of new roads and the upgrading of others by the state in cooperation with the federal government. The study shows that construction of roads was more progressive when Sabah was part of the Malaysia federation than when the state was under the British. This is because the road construction linked a large part of Sabah, including the West Coast, East Coast and the Interior areas. The development of roads contributed to socioeconomic change in Sabah which was visible in the increased agricultural productivity and improvements in the industrial sector. The building of roads also contributed towards economic growth as evident in the increase in new settlement areas, employment opportunities and demographic change in Sabah.